(untitled) (Journal of Imam Al-Kadhim College, 2026)
This study aims to analyze the directions of urgent news coverage of the “Israeli” military escalation against Iran on Al Jazeera and Al Arabiya Al Hadath, by examining the news sources, topics, and sub-categories included in the coverage. The research falls within descriptive–inferential studies and employs quantitative content analysis using a systematic random sample of 1,200 news items drawn from a total of 10,404 urgent news items broadcast by the two channels over eleven days. The study relied on a structured content analysis form. The findings reveal clear differences between the channels: Al Jazeera relied more on official sources and news agencies, with greater emphasis on political and humanitarian topics and the Iranian narrative, alongside a multi-party security framing. In contrast, Al Arabiya Al Hadath relied more heavily on unspecified media sources, correspondents, and private sources, with a stronger focus on military topics, “Israeli” security precautions, and highlighting civilian casualties on both sides.